2014
DOI: 10.5603/ep.2014.0014
|View full text |Cite
|
Sign up to set email alerts
|

Kwas zoledronowy stosowany przez dwa lata u Chinek z osteoporozą pomenopauzalną zwiększa gęstość mineralną tkanki kostnej i poprawia jakość życia związaną ze stanem zdrowia

Abstract:  Zoledronic acid increases bone mineral density and improves health-related quality of life over two years of treatment in Chinese women with postmenopausal osteoporosisKwas zoledronowy stosowany przez dwa lata u Chinek z osteoporozą pomenopauzalną zwiększa gęstość mineralną tkanki kostnej i poprawia jakość życia związaną ze stanem zdrowia AbstractIntroduction: Osteoporosis is characterised by decreased bone mass and weakened bones, with an increased risk of fractures. Osteoporotic fracture, the most serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Despite increasing evidence showing worse QOL in OP patients, little is known regarding interventions improving QOL, particularly in elderly patients. Recently, a study in China has found over two years of zoledronic acid treatment in women with postmenopausal OP can improve bone mineral density, and can help improve QOL[10]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing evidence showing worse QOL in OP patients, little is known regarding interventions improving QOL, particularly in elderly patients. Recently, a study in China has found over two years of zoledronic acid treatment in women with postmenopausal OP can improve bone mineral density, and can help improve QOL[10]. …”
Section: Introductionmentioning
confidence: 99%
“…Another study of zoledronic acid using Qualeffo over 12 months in women with a T score -2.5 or lower also showed an improvement of 20% in pain scores [15]. The least improvement was 7% using Zoledronic acid in women with T scores at the femur or spine below T-2.5 after 24 months [16]. The present study covers a median treatment time of 9 yr in the course of which there was a 26% improvement in pain in female patients (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 95%
“… 15 , 16 Zoledronic acid (ZOL) is a third-generation, nitrogen-containing bisphosphonate, and a once-yearly intravenous infusion of ZOL 5 mg can ensure bisphosphonate adherence and persistence over 12-month interval. 17 , 18 Moreover, ZOL is the most potent inhibitor of farnesyl diphosphate synthase, resulting in strongly inhibiting bone resorption, increasing secondary mineralization for refilling of remodeling space and reducing the incidence of vertebral/non-vertebral fractures. 19 The therapeutic effect of PKP combined with ZOL infusion in the treatment of elderly OVCF is currently controversial.…”
Section: Introductionmentioning
confidence: 99%